Pengendalian Pencemaran Sumber Daya Air Sungai Kuantan dan Sungai Singingi dengan Pendekatan Kearifan Lokal (Local Wisdom) di Kabupaten Kuantan Singingi - Tasriani Tasriani; Trian Zulhadi (Kutubkhanah, 2013)
The purpose of this study was to determine the impact of gold mining Without Permission (PETI) to Kuantan river and the pollution of Singingi river in Kuantan Singingid district. This research has more or less three months. This study uses primary data by conducting observations and interviews directly to the concept of local knowledge (local wisdom) as an approach that is able to address the impact of the Gold Mining Without Permission (PETI) in Kuantan river pollution control and Singingi river in Kuantan district. The study found several factors from the Gold Mining Without Permission (PETI) in Kuantan Singingi District, among others: 1) the current economic factors, 2) lack of knowledge society impact factor of the Gold Mining Without Permission, 3) lack of public awareness of the importance of factors maintaining natural about, 4) government regulation factor is still weak, it means the government is still half -and-half in combating Gold Mining Without this license, 5) there are strict sanctions earlier, and 6) the unavailability of the customary rules of law which can be used for society belle. For the wisdom of this research needs to be reviewed again and used as a tool to control pollution in Kuantan river and Singingi river in the present and in the future.